2009
DOI: 10.1074/jbc.m109.022855
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Administration of KB-R7943 Induces Up-regulation of Cardiac NCX1

Abstract: The NCX1 (sodium-calcium exchanger) is up-regulated in human heart failure and in many animal models of heart failure. The potential benefits and risks of therapeutically blocking NCX1 in heart failure and during ischemia-reperfusion are being actively investigated. In this study, we demonstrate that prolonged administration of the NCX1 inhibitor KB-R7943 resulted in the up-regulation of Ncx1 gene expression in both isolated adult cardiomyocytes and intact mouse hearts. Ncx1 up-regulation is mediated by the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…2, A and B) to try to compensate for the ouabain-induced reduction in pump activity. This parallels a recent report (78) showing that the chronic inhibition of NCX in cardiac myocytes induces a compensatory upregulation of NCX1 in those cells.…”
Section: Discussionsupporting
confidence: 90%
“…2, A and B) to try to compensate for the ouabain-induced reduction in pump activity. This parallels a recent report (78) showing that the chronic inhibition of NCX in cardiac myocytes induces a compensatory upregulation of NCX1 in those cells.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, an increase in abnormal Reelin would result in less activation of the Reelin signaling pathway and could contribute to the generation of a vicious cycle, where Reelin up-regulation may be driven by a chronic failure in Reelin signaling. Up-regulation of proteins in response to chronic inhibition is a recognized phenomenon documented for several proteins [2830]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, p38 has the potential to affect myocyte contractility by promoting transcription of the Na + /Ca 2+ exchanger (NCX1), a key regulator of Ca 2+ homeostasis in both the healthy and pathological myocardium (271). Interestingly, a recent study found that inhibiting NCX1 actually resulted in upregulation of the NCX1 gene in a p38-dependent manner and that this increase was accompanied by NCX-p38 complex formation (441). With the proposal of NCX1 inhibitors as a therapeutic treatment for heart failure, more work needs to be done to better understand the interplay between these two proteins.…”
Section: Mitogen-activated Protein Kinases In Heart Function and mentioning
confidence: 99%